Tolvaptan and Kidney Pain in Patients With Autosomal Dominant Polycystic Kidney Disease: Secondary Analysis From a Randomized Controlled Trial - Casteleijn, Niek F. (Am J Kidney Dis, 2016)
BACKGROUND: Kidney pain is a common complication in patients with autosomal dominant polycystic kidney disease (ADPKD), and data from the TEMPO 3:4 trial suggested that tolvaptan, a vasopressin V2 receptor antagonist, may have a positive effect on kidney pain in this patient group. Because pain is difficult to measure, the incidence of kidney pain leading to objective medical interventions was used in the present study to assess pain. STUDY DESIGN: Secondary analysis from a randomized controlled trial. SETTING & PARTICIPANTS: Patients with ADPKD with preserved kidney function. INTERVENTION: Tolvaptan or placebo. OUTCOMES: Kidney pain events defined by objective medical interventions. MEASUREMENTS: Kidney pain events were recorded and independently adjudicated. Incidence of a first kidney pain event was assessed overall and categorized into 5 subgroups according to severity. RESULTS: Of 1,445 participating patients (48.4% women; mean age, 39 ± 7 [SD] years; mean estimated glomerular filtration rate, 81 ± 22 mL/min/1.73 m(2); median total kidney volume, 1,692 [IQR, 750–7,555] mL), 50.9% reported a history of kidney pain at baseline. History of urinary tract infections, kidney stones, or hematuria (all P < 0.001) and female sex (P < 0.001) were significantly associated with history of kidney pain. Tolvaptan use resulted in a significantly lower incidence of kidney pain events when compared to placebo: 10.1% versus 16.8% (P < 0.001), with a risk reduction of 36% (HR, 0.64; 95% CI, 0.48–0.86). The reduction in pain event incidence by tolvaptan was found in all groups irrespective of pain severity and was independent of predisposing factors (P for interaction > 0.05). The effect of tolvaptan was explained at least in part by a decrease in incidence of urinary tract infections, kidney stones, and hematuria when compared to placebo. LIMITATIONS: Trial has specific inclusion criteria for total kidney volume and kidney function. CONCLUSIONS: Tolvaptan decreased the incidence of kidney pain events independent of patient characteristics predisposing for kidney pain and possibly in part due to reductions in ADPKD-related complications.